Synthesis of azido end-functional polystyrene: Azidoethyl-2-bromo-2-methylpropanoate initiator and effect of time on polymerization - Jubaraj Chandra; Farhana Sumi Rain; Tariqul Hasan; Roushown Ali (Advanced Industrial and Engineering Polymer Research, 2021)
Azidoethyl-2-bromo-2-methylpropanoate (AEBMP) has been synthesized from 2-azidoethanol and 2-bromo-2-methylpropionyl bromide under nitrogen atmosphere. The azido end-functional polystyrene (PS-N3) has been synthesized by Atom Transfer Radical Polymerization (ATRP) technique using AEBMP initiator and styrene in conjugation with Cu(1)Br-bipyridine catalyst at 100°C. The polymerization was performed at three different periods of time, and it was found that both yield and number average molecular weight were increased linearly with increasing reaction time. Thermogravimetric analysis showed that the polystyrene is stable up to 300°C. The molecular weight of the polystyrene was determined using Gel Permeation Chromatography (GPC), and structures of the initiator AEBMP and polystyrene (PS-N3) were characterized by 1H NMR and FT-IR spectroscopy.